2021
DOI: 10.1186/s40249-021-00884-7
|View full text |Cite
|
Sign up to set email alerts
|

Preventive behaviours and family inequalities during the COVID-19 pandemic: a cross-sectional study in China

Abstract: Background The coronavirus disease 2019 (COVID-19) pandemic is an international public health threat, and people's participation in disease-related preventive behaviours is the key to controlling infectious diseases. This study aimed to assess the differences in adopting preventive behaviours among populations to explore potential individual and household factors and inequalities within families. Methods This online survey was conducted in April 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 58 publications
2
10
0
Order By: Relevance
“…Public health organizations have been striving to develop behavioral interventions to promote individual preventive behaviors among the general population including older adults [ 10 ]. However, evidence has indicated that older adults showed a relatively low compliance with preventive behaviors compared to other age groups [ 11 ]. Identifying key correlates of the preventive behaviors that are potentially modifiable through intervention (e.g., social-cognitive factors), that can be targeted in messages or campaigns of behavioral intervention aimed at promoting preventive behaviors among older adults, is a recognized priority.…”
Section: Introductionmentioning
confidence: 99%
“…Public health organizations have been striving to develop behavioral interventions to promote individual preventive behaviors among the general population including older adults [ 10 ]. However, evidence has indicated that older adults showed a relatively low compliance with preventive behaviors compared to other age groups [ 11 ]. Identifying key correlates of the preventive behaviors that are potentially modifiable through intervention (e.g., social-cognitive factors), that can be targeted in messages or campaigns of behavioral intervention aimed at promoting preventive behaviors among older adults, is a recognized priority.…”
Section: Introductionmentioning
confidence: 99%
“…We found social inequalities in information-seeking behavior intensity within China. Studies have confirmed that deprived populations show relatively lower awareness of infectious diseases, including H1N1 and COVID-19 10 , 32 , 33 . In our findings, these inequalities are evidenced by the absolute change in Baidu Index volume as well as the speed with which peak search volume is achieved.…”
Section: Discussionmentioning
confidence: 92%
“… 53 Indeed, a study by Ye et al reported people who shared their activities with others or interacted with friends were more likely to take preventive measures for the COVID-19. 54 However, as misinformation regarding the COVID-19 by non-experts through online networks can be disseminated and sometimes affect negatively the population mental health, 55 the reliance only on social networking service for social interactions may be a double-edged sword in such a special time.…”
Section: Discussionmentioning
confidence: 99%